Assessment of renal function in the anaesthetised rat following injection of superparamagnetic iron oxide nanoparticles - Gobbo, Oliviero; Edge, Deirdre; Shortt, Christine M.; Johns, E.J.; Markos, Farouk; Abdulla, Mohammed H.; Barry, Elaine F. (My University, 2017)
A recent study showed that a significant fall in mean arterial pressure (MAP) occurred following intravenous injection of two novel superparamagnetic iron oxide nanoparticles (SPIONs), MF66 and OD15. To assess if this was caused by excessive glomerular clearance, the effect of both particles on renal function was studied. Experiments were performed on sodium pentobarbital anaesthetised male Wistar rats (250–350 g). Twenty-minute urine clearances were taken followed by an i.v. bolus of MF66, OD15 (2 mg·kg–1), or dH2O (0.4 mL·kg–1). MF6 or OD15 injection resulted in a significant transient drop in MAP and renal blood flow by approximately 33% and 50% (P < 0.05). The absolute excretion of sodium was significantly increased (P < 0.05) by almost 80% and 70% following OD15 and MF66, respectively. Similarly, fractional excretion of sodium was increased by almost 80% and 60% following OD15 and MF66, respectively. The glomerular filtration rate was not significantly affected, but urine flow increased nonsignificantly by approximately 50% and 66% following i.v. injection of OD15 and MF66, respectively. SPIONs produce a decrease in blood pressure and a natriuresis; however, the rate of fluid filtration in the kidney was not significantly affected.
PUBLISHED
Keywords: Supermagnetic nanoparticles; Renal function; Glomerular clearance